Ethnobotanical survey, anthelmintic effects and cytotoxicity of plants used for treatment of helminthiasis in the Central and Kara regions of Togo - Essoham Ataba; Gnatoulma Katawa; Manuel Ritter; Adjoa Holali Ameyapoh; Kokou Anani; Oukoe M. Amessoudji; Pélagie Edlom Tchadié; Tchadjabo Tchacondo; Komlan Batawila; Yaovi Ameyapoh; Achim Hoerauf; Laura E. Layland; et al. (BMC, 2020)
Abstract Background Traditional medicines are the main source of treatment of helminthiasis in endemic areas of Togo. The present study aimed to investigate the plants used by Traditional healers (THs) to treat helminth infections in endemic communities within the Central and Kara regions of Togo and to evaluate the anthelmintic activity of the three most cited plants. Methods An ethnobotanical survey was conducted from 19 to 24 June 2017 among traditional healers in the Central and Kara regions of Togo. The anthelmintic activity of the most cited plants namely Aframomum melegueta K. Schum, Khaya senegalensis A. Juss and Xylopia aethiopica A. Rich, was evaluated using microfilariae (Mf) of Litomosoides sigmodontis. The plants were evaluated for cytotoxicity according to the recommendation of NF EN ISO 10993-5 standard using the propidium iodide (PI) dye by flow cytometry on human peripheral blood mononuclear cells. Results A total of 197 THs were interviewed and 41 plant species were recorded. Leguminosae (14.6%) and Annonaceae (9.7%) families constitute the highest number of species cited for treatment of helminth infections. Afromomum melegueta was the most cited by the THs for the treatment of onchocerciasis (UV = 0.036) while X. aethiopica was associated with the treatment of schistosomiasis (UV = 0.061) and lymphatic filariasis (UV = 0.061). There was a great agreement among the THs regarding ethnomedicinal uses of plants to treat helminthiasis with ICF values ranging from 0.57 to 0.67. The anthelmintic assay yielded lethal doses values of 233 μg/mL, 265 μg/mL and 550 μg/mL, respectively for X. aethiopica, A. melegueta and K. senegalensis. Afromomum melegueta and X. aethiopica presented no cytotoxicity, less than 20% death, whereas K. senegalensis induced moderate toxicity, 24 ± 8% death. Conclusion This study demonstrated the scientific rationale for the use of plants to treat helminthiasis in the Togolese traditional medicine. However, the use of K. senegalensis requires more caution since the plant is fairly toxic. Trial Registration NA